Raspberry Supplementation Attenuates Blood Pressure and Improves Mesenteric Artery Relaxation in a Nitric Oxide-Independent Mechanism in Angiotensin II-Treated Rats. (14th June 2022) - Danh, Jessica; Zheng, Xiaoxu; Meister, Maureen; Najjar, Rami; Wanders, Desiree; Feresin, Rafaela
Abstract: Objectives: Berries are rich in polyphenols with strong antioxidant capacity. They have been suggested to exert antihypertensive properties, which may be due to an increase in the levels of endothelial nitric oxide (NO), a potent vasodilator. Thus, the objective of this study was to evaluate the effects of raspberry supplementation on vascular function in angiotensin (Ang) II-treated rats. Methods: Eight-week-old Sprague-Dawley rats ( n = 8/group) were fed an AIN-93M diet (control, Ang II, and Losartan (LOS; 20 mg/kg/BW) groups) or AIN-93M diet supplemented with 10% w/w freeze-dried raspberry (RB + Ang II) for 7 weeks. At week 5, rats were implanted with subcutaneous osmotic minipumps that delivered 0.9% saline (CON) or Ang II (270 ng/kg BW/min) for an additional 3 weeks. Blood pressure (BP) was measured using tail-cuff plethysmography ( n = 7–8/group). First order mesenteric arteries were isolated for vascular relaxation measurements following constriction by U46619 (1 μM) in a wire myograph ( n = 3–8/group). Data were found to be normal and analyzed using ANOVA or mixed-model where appropriate. Results: Ang II group showed a significant increase in systolic BP (SBP) (+26.8%, p = 0.002) 2 weeks after implantation as compared to baseline, while CON, RB + Ang II, and LOS groups showed no differences. Final SBP was significantly lower in the CON (−26.4%, p = 0.01), LOS (−28.3%, p = 0.0005), and RB + Ang II (−20.8%, p = 0.03) groups compared to Ang II group. Relaxation was significantly inhibited in the Ang II group in the presence of acetylcholine after incubation with L-NAME (100 μM), a NO synthase inhibitor, when compared to LOS (p = 0.0003) and RB + Ang II (p = 0.0004) groups. Similarly, relaxation in the Ang II group was significantly inhibited after incubation with ODQ (10 μM), a sGC inhibitor, when compared to CON (p = 0.0002), LOS (p = 0.0004), and RB + Ang II (p = 0.0001) group. No significant changes in vessel relaxation were observed after incubation with LY294002 (20 μM), a PI3K inhibitor. Conclusions: We demonstrate that RB supplementation attenuated Ang II-induced hypertension and abolished the inhibitory effects of L-NAME and ODQ. This suggests that RB may exert its vasodilatory effects in a NO-independent manner. Funding Sources: The Agriculture and Food Research Initiative (grant no. 2019–67, 017-29, 257/project accession no. 1, 018, 642) from the USDA National Institute of Food and Agriculture.